Binding of dipeptidyl peptidase III to the oxidative stress cell sensor Kelch-like ECH-associated protein 1 is a two-step process. Issue 18 (12th December 2021) - Matić, Sara; Kekez, Ivana; Tomin, Marko; Bogár, Ferenc; Šupljika, Filip; Kazazić, Saša; Hanić, Maja; Jha, Shalinee; Brkić, Hrvoje; Bourgeois, Benjamin; Madl, Tobias; Gruber, Karl; et al.
Abstract: This work is about synergy of theory and experiment in revealing mechanism of binding of dipeptidyl peptidase III (DPP III) and Kelch-like ECH-associated protein 1 (KEAP1), the main cellular sensor of oxidative stress. The NRF2 ̶ KEAP1 signaling pathway is important for cell protection, but it is also impaired in many cancer cells where NRF2 target gene expression leads to resistance to chemotherapeutic drugs. DPP III competitively binds to KEAP1 in the conditions of oxidative stress and induces release of NRF2 and its translocation into nucleus. The binding is established mainly through the ETGE motif of DPP III and the Kelch domain of KEAP1. However, although part of a flexible loop, ETGE itself is firmly attached to the DPP III surface by strong hydrogen bonds. Using combined computational and experimental study, we found that DPP III ̶ Kelch binding is a two-step process comprising the endergonic loop detachment and exergonic DPP III ̶ Kelch interaction. Substitution of arginines, which keep the ETGE motif attached, decreases the work needed for its release and increases DPP III ̶ Kelch binding affinity. Interestingly, mutations of one of these arginine residues have been reported in cBioPortal for cancer genomics, implicating its possible involvement in cancer development. Communicated by Ramaswamy H. Sarma